Spectral function of graphene with short-range impurity centers: Graphene and graphite multilayers - Skrypnyk, Yu.V.; Loktev, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Spectral function of graphene with point substitutional defects is calculated for different impurity concentrations. It is demonstrated that features in the spectral function of graphene observed in ARPES experiments can be caused by the presence of a well-defined resonance state and are clearly pronounced at the impurity concentrations, which are of the order of the critical concentration for the impurity induced spectrum rearrangement.